Efficient removal of salts from the residual dross of aluminium melting - Illés, István; Zakiyya, Hanna; Kékesi, Tamás (International Journal of Engineering and Management Sciences, 2019)
A residual dross of high quantity and high salt content arises from the hot (thermo-mechanical) treatment of the primary dross generated by the production of aluminium alloys from scrap. It contains a relatively low concentration of metal (5 – 10 %) but a high amount (30 - %) of chloride salts and some other components beside the oxide matrix. Due to the components dissolved in or reacted with water, this industrial residue - arising in thousands of tons also in Hungary – qualifies as hazardous and causes a real burden to the environment. According to the laboratory experiments aimed at an economical technology, the chlorides are dissolved within a few minutes when a liquid/solid ratio of 1:1 cm3/g (water volume:sample mass) is assured with an intensity of the horizontal shaking to prevent sedimentation. However, the filling ratio of the vessel also appears to have an effect. An implementation of relatively low cost would allow the recycling of the salt and the application of the final residue for alternative purposes.